Intelligent conflict detection and awareness for UAVs - Albaker, B.M.; Rahim, N.A. (2009)
The deployment of unmanned aerial vehicles into the airspace is directly related to their ability to detect and avoid other aircraft objects. Through the performance analysis of the conflict detection and avoidance requirement, conceptual functional architecture of the conflict detection and conflict awareness are proposed with a method to extract collision parameters. These parameters include collision points, time to collision, collision interval and collision angle. The method is based onto monitoring the environment and sharing of flight plan segments among conflicting aircraft. The detection of a potential conflict is achieved by projecting states of the conflicting aircrafts' flight plans in the near future. In addition, the method estimates a suitable time to activate avoidance model and pass extracted collision parameters to that model. That is, in order to handle the maneuvering commands and thereby avoid conflicts.